2018
DOI: 10.1159/000487126
|View full text |Cite
|
Sign up to set email alerts
|

The Trend of β<sub>3</sub>-Adrenergic Receptor in the Development of Septic Myocardial Depression: A Lipopolysaccharide-Induced Rat Septic Shock Model

Abstract: Septic shock with low cardiac output is very common in children. However, the mechanism underlying myocardial depression is unclear. The role of β3-AR in the development of myocardial depression in sepsis is unknown. In the present study, we generated an adolescent rat model of hypodynamic septic shock induced by lipopolysaccharide (LPS). Neonatal cardiomyocytes were also treated with LPS to mimic myocardial depression in sepsis, which was confirmed via an in vivo left ventricular hemodynamic study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…As mentioned previously [ 2 , 12 ], our group has found that there is a positive relationship between the MAP and heart function. In this study, septic shock occurred at approximately 2 hours after LPS injection, and the MAP of the control groups remained unchanged ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…As mentioned previously [ 2 , 12 ], our group has found that there is a positive relationship between the MAP and heart function. In this study, septic shock occurred at approximately 2 hours after LPS injection, and the MAP of the control groups remained unchanged ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 73%
“…Briefly, male adolescent rats (Changsheng Bio, Benxi, China) weighing 170 g to 190 g were anesthetized with 20% urethane (1 g/kg, 1 g urethane was added to 5 mL 0.9% saline). We separated the left femoral artery and connected it to the electrophysiological recorder (Biopac MP150 Biopac Systems, Goleta, CA, USA) to monitor the pressure and injected LPS intraperitoneally to establish the model (20 mg/kg, 10 mg LPS was added to 1 mL 0.9% saline) (Escherichia coli 055: B5, L-2880, Sigma-Aldrich, St. Louis, MO, USA) [ 2 ]. Control rats were treated with an equal volume of saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that there is a positive relationship between mean arterial pressure (MAP) and heart function 10 . Therefore, we measured MAP and found that MAP started to decline approximately 1.5 h after the administration of LPS.…”
Section: Resultsmentioning
confidence: 89%
“…All experiments conformed to all relevant regulatory standards. The adolescent rat model of septic shock was generated by intraperitoneal injection of LPS, as in our previous description 10 . Briefly, male pathogen-free Wistar rats from Changsheng Bio (Benxi, China) weighing from 170 to 190 g were anesthetized by 20% urethane (1 g/kg i.p.).…”
Section: Methodsmentioning
confidence: 99%